Bridging the Gap: From Biomechanics and Functional Morphology of Plants to Biomimetic Developments - Olga Speck; Thomas Speck (Biomimetics, 2021)
During the last few decades, biomimetics has attracted increasing attention in both basic and applied research and in various fields of industry and building construction [...]